Genetic study on the impact of rs320 lipoprotein lipase polymorphism on dyslipidemia among Javanese Indonesians with type 2 diabetes mellitus - Christine Patramurti; Dita Maria Virginia (Pharmaciana, 2026)
Dyslipidemia commonly co-occurs with type 2 diabetes mellitus (T2DM), acting as a major factor in the elevated incidence of cardiovascular disease (CVD) within this population. One of the factors that raises the risk of dyslipidemia in people with T2DM is lipoprotein lipase (LPL) polymorphisms, particularly the rs320 variant. Associated with lipid metabolic pathways, the LPL rs320 genetic variant is considered a potential contributor to the dyslipidemia observed in several populations with T2DM. The influence of rs320 on dyslipidemia in individuals with T2DM, particularly among Javanese, remains uncertain. The objective of this study is to examine how the rs320 polymorphism affects dyslipidemic profiles among Javanese Indonesian individuals suffering from T2DM. This study included 103 Javanese individuals with T2DM. We detected the rs320 allele using the tetra-primer amplification refractory mutation system-based polymerase chain reaction (T-ARMS-PCR) method. We analyzed the participants' lipid profiles, with enzymatic methods used to measure serum triglycerides (TGs), total cholesterol (TC), and both high-density and low-density lipoprotein cholesterol (HDL-C and LDL-C). We assessed the association of the rs320 allele with dyslipidemia using chi-square tests. Our findings indicated that the rs320 allele was not significantly associated with dyslipidemia among Javanese individuals diagnosed with T2DM (χ² = 0.016, p = 0.900). This suggests the rs320 allele may not contribute to dyslipidemia, although other factors may play a role in Javanese people with type 2 diabetes. Further investigation is needed to identify genetic determinants of dyslipidemia in patients with type 2 diabetes and to potentially enhance personalized medicine based on individual genetics.